Blockchain governance - Aron Fischer; María-Cruz Valiente (Internet Policy Review, 2021)
Blockchain governance can be regarded as the integration of norms and culture, the laws and the code, the people and the institutions that facilitate coordination and together determine a given organisation.
Keywords: 300; Blockchain; Governance